Use of Intraoperative Frozen Section in the Surgical Management of Patients with Nonmelanoma Skin Cancer. (1st November 2021) - Loh, LiAnn; Tiwari, Priya; Lee, Jingtzer; Low, O-Wern; Nallathamby, Vigneswaran; Lee, Hanjing; Lim, Jane; Lim, Thiam Chye; Yap, Yan Lin
Abstract : Background . Intraoperative frozen section (IFS) is often utilised in the surgical treatment of nonmelanocytic skin cancer (NMSC) in sensitive facial regions when Mohs micrographic surgery (MMS) is not available. Objective . To compare the outcome of NMSC patients with excision performed with and without IFS. Materials and Methods . A retrospective, single-centre study was performed on all patients who had undergone resection of NMSC with and without IFS control at the National University Hospital (NUH) from 2010 to 2015. Results . 116 patients were recruited, of which 86 had IFS and 30 did not. The complete excision rate of patients with IFS was higher at 87.2% (p = 0.0194 ), need for secondary operation was lower at 1.2% (p = 0.005 ), and need for postsurgery radiotherapy or chemotherapy was lower at 1.2% (p = 0.001 ). The average duration of surgery in patients who underwent IFS was 95.4 minutes compared to 70.1 minutes in cases which did not undergo IFS. Conclusion . Our study showed an increased complete excision rate and reduced need for secondary surgeries and adjuvant therapy in patients with IFS. However, a longer operative duration was required. Use of IFS may be useful in patients with NMSC lesions in sensitive regions requiring complex reconstruction after tumour excision.